The Nutrition Content of Oyster Mushroom and Spinach Flour Alternative Food Processed Ingredients - Rahmawati Rahmawati (Universitas Tanjungpura, 2020)
Oyster mushroom and spinach flour are food preparations that are made through drying and milling processes in order to maintain shelf life. This study aimed to determine the nutritional content of oyster mushroom flour and spinach as an alternative for food processing. This study used a proximate test analysis presented descriptively based on the average results of chemical analysis with 3 treatments. Proximate analysis in the form of crude were protein, water, ash, crude fat, carbohydrate by difference and crude fiber content using the AOAC method, as well as iron content using the spectrophotometric method. The results of the study showed that oyster mushroom flour contains high fiber (27.22 g), protein (23.26 g), and iron (5.80 g), while fiber content (7.56, g), protein (3 , 05 g), and iron (1.80 g) of spinach flour is relatively low. Even so, these two potential foods have very good nutritional value for consumption. Therefore, oyster mushrooms and spinach can be an alternative substitution and fortification of processed food to increase nutrient content.